Clinical and ultrasonographic features in anterior ischemic optic neuropathy - Jianu, Dragos Cătălin; Jianu, Silviana Nina; Munteanu, Mihnea; Petrica, Ligia (Vojnosanitetski pregled, 2020)
Background/Aim. Anterior ischemic optic neuropathy (AION) represent a segmental infarction of the optic nerve head which is supplied by the posterior ciliary arteries. There are two types of AION: non-arteritic (NA-AION and arteritic (A-AION), due to giant cell arteritis (GCA). The aim of this study was to investigate the clinical features and ultrasound characteristics of the orbital vessels and superficial temporal and carotid arteries, in patients with unilateral acute AION in order to help differentiate newly diagnosed NA-AION from A-AION. Methods. In this prospective comparative, observational study, 62 consecutive patients with clinical suspicion of unilateral acute AION were examined at admission and in the first two months of evolution, following a protocol including color Doppler imaging (CDI) of the orbital vessels. Results. We found 12 patients with A-AION, all of them with biopsy-confirmed disease, and 50 patients with NA-AION. A-AION patients presented a combination of a history of amaurosis fugax before acute, painless, and severe vision loss in the affected eye, and a diffuse pale optic disc edema. In these patients, CDI of the orbital vessels indicated high resistance index (RI), with severe diminished blood flow velocities in all orbital vessels, in both orbits. In the NA-AION patients, none of these clinical symptoms were found and blood velocities and RI in posterior ciliary arteries were preserved. Typical sonographic feature in temporal arteritis as part of GCA was the „dark halo” sign. Conclusions. The ultrasound investigations enable prompt differentiation between NA-AION and A-AION.
Keywords: optic neuropathy, ischemic; risk factors; giant cell arteritis; diagnosis, differential; ultrasonography, doppler, color.